Serum and follicular fluid levels of soluble receptor for advanced glycation end-products in women with and without polycystic ovary syndrome - Neda Emami; AliReza Alizadeh; Arezoo Maleki-Hajiagha; Alireza Dizavi; Samira Vesali; Ashraf Moini (BMC, 2023)
Abstract Background Advanced glycation end products (AGEs) are known to associate with the pathogenesis of several chronic diseases via interaction with their corresponding receptor (RAGE). The soluble forms of RAGE (sRAGE) are considered as anti-inflammatory agents by inhibiting the consequent adverse effects of AGE. We aimed at comparing sRAGE levels in the follicular fluid (FF) and serum of women with or without Polycystic Ovary Syndrome (PCOS) who underwent controlled ovarian stimulation for in vitro fertilisation (IVF). Methods A total of forty-five eligible women (26 non-PCOS (control) and 19 patients with PCOS (case)) were included the study. sRAGEs in FF and blood serum were measured using ELISA kit. Results No statistically significant differences were found in FF and serum sRAGE between case and control groups. Correlation analysis showed a significant and positive relationship between serum levels of sRAGE and FF sRAGE in PCOS (r = 0.639; p = 0.004), in control participants (r = 0.481; p = 0.017), and in total participants (r = 0.552; p = 0.000). Data revealed a statistically significant difference in FF sRAGE concentration among all participants by body mass index (BMI) categories (p = 0.01) and in controls (p = 0.022). Significant differences were found for all the nutrients and AGEs consumption according to Food Frequency Questionnaire in both groups (p = 0.0001). A significant reverse relationship was found between FF levels of sRAGE and AGE in PCOS (r = -0.513; p = 0.025). The concentration of sRAGE in serum and FF is the same in PCOS and control. Conclusion The present study revealed for the first time that there are no statistically significant differences between the concentration of serum sRAGE and FF sRAGE among Iranian women with and without PCOS. However, BMI and dietary intake of AGEs have more significant effects on sRAGE concentration in Iranian women. Future studies in developed and developing countries with larger sample sizes are required to determine the long-term consequences of chronic AGE over consumption and the optimal strategies for minimizing AGE-related pathology, specifically in low income and developing countries.